Numerical analysis of geometrically induced hardening in planar architectured materials. (1st February 2020) - Siska, Filip; Cizek, Jan; Seiner, Hanus; Dlouhy, Ivo
Abstract: The presented study focuses on the evaluation of mechanical performance of architectured materials with planar geometry. The main objective is to investigate the effect of geometrically induced hardening of different geometrical patterns during uniaxial loading. The analysis is performed by FEM on a basic cell that represents a particular geometry. Seven different geometries, each with three volume fractions of the reinforcement (0.1, 0.4 and 0.8) are analyzed for four combinations of perfect plastic materials. The matrix material is kept identical, while 4 variants of the reinforcement material are taken into account. The results show that geometry can induce hardening that expands the region of a stable material deformation beyond the capabilities of its constituent materials. An improvement in the strain energy density due to the hardening can be achieved either by a higher strength attained by using the reinforcement aligned to the loading direction, or by a higher strain attained by using the reinforcement arranged like cantilever beam that is inclined or perpendicular to the loading. The best performance regarding strain energy density among the different volume fractions and materials combinations is achieved for the geometry with a combination of both types of reinforcement.